KESESUAIAN TAHAPAN KEGIATAN PKM MAHASISWA PRODI PENDIDIKAN VOKASIONAL KONSTRUKSI BANGUNAN UNJ - Anita Komala Dewi; Santoso Sri Handoyo; Arris Maulana (LPPM Universitas Negeri Jakarta, 2019)
This research aims to Suitability Of The Stages PKM Activities Of Vocational Education Study Program Building Construction Students UNJ contained in the Guidebook of PKM UNJ. This research was conducted in Prodi Vocational Education Building Construction FT UNJ and SMK Negeri in Jakarta. The time of this study was conducted in February-March 2018. This research uses descriptive research with quantitative approach. Data collection tehniques used in this research is a questionnaire distributed to students who do PKM in the 106th semester and 107th semester, and interviews submitted to Tutor Teachers as a research data amplifier obtained from the questionnaire. The population in this research is 75 students who follow PKM in the 106th semester and 107th semester, for 42 Tutor Teachers. The sample is 65 students and 22 Tutor Teachers. Data analysis technique in this research is Descriptive Statistic. The results of this research shows that the implementation of PKM students Study Program of Vocational Education Building Construction is mostly in accordance with the stages of PKM activities , with a percentage of 65,21% in observation and orientation activies, 48,78% in guided teaching exercises, 61,79% at independent teaching exercises, 81,92% on exam preparation, and 86,93% on final exams and graduation students.